Ceramic dielectric material as well as preparation method and application thereof
By using BaTiO3 and eutectics of elements Bi, Li, and B in ceramic capacitors, combined with low temperature sintering technology, the problems of high sintering temperature and insufficient density of barium titanate materials are solved, and the thermal stability of ceramic dielectric materials is significantly improved and density, thereby improving the mechanical strength and dielectric properties of multi-layer ceramic capacitors.
Patent Information
- Application Number
- CN202411406871.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
AI Technical Summary
The sintering temperature of barium titanate material in existing ceramic capacitors is high, excessive or uneven distribution of sintering aids leads to a decrease in thermal stability and insufficient density, which affects mechanical strength and dielectric properties.
Using ceramic dielectric materials including BaTiO3 and eutectic substances, Bi, Li, and B elements are added to the eutectic substances. Through low-temperature sintering technology and multi-step sintering process, Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-Li, Ba -Bi-B, Bi-Li-B eutectics reduce sintering temperature, relieve lattice stress, promote densification and uniform liquid phase distribution.
It achieves good thermal stability and density of ceramic dielectric materials, and improves the mechanical strength, dielectric properties and reliability of multi-layer ceramic capacitors.
Smart Images

Figure BDA0005076863890000061 
Figure BDA0005076863890000071 
Figure BDA0005076863890000072
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic dielectric materials, and in particular relates to a ceramic dielectric material and a preparation method and application thereof. Background Art
[0002] Multilayer ceramic capacitors (MLCCs) are chip-type electronic components widely used in electronic products, automotive appliances, and military equipment. The goal is to obtain high-capacitance MLCCs with strong reliability and better dielectric properties to meet the needs of the ever-growing production and life.
[0003] In MLCC, barium titanate-based ceramic materials as ceramic dielectrics play a decisive role in the reliability and dielectric properties of capacitors. In order to obtain higher dielectric constants and higher mechanical strength, low-temperature sintering technology is usually used to obtain high-quality ceramic materials, such as microwave sintering, electric field sintering or flash sintering technology, which respectively realize the sintering process through microwave energy, current heating or high pressure and high temperature in a very short time. However, in the actual sintering process, it is still necessary to add sintering aids to reduce the sintering temperature of barium titanate and realize the sintering densification process. Excessive introduction or uneven distribution of sintering aids will lead to a decrease in the thermal stability of barium titanate, and the sintering temperature of the above-mentioned low-temperature sintering technology is still generally above 900°C. Some low-temperature sintering aids are easy to volatilize or decompose at high temperatures, affecting the sintering process of the material, and may even cause excessive residual stress or internal defects in the material, and cannot well control the grain growth and distribution during the sintering process, resulting in insufficient densification of the barium titanate material obtained by sintering, thereby reducing the mechanical strength, dielectric properties and reliability of the MLCC.
[0004] Therefore, there is an urgent need to provide a ceramic dielectric material having good thermal stability and density. Furthermore, the MLCC prepared using the ceramic dielectric material has good mechanical strength, dielectric properties and reliability. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art, and at least provide a beneficial choice or create conditions. Specifically, the present invention provides a ceramic dielectric material, which has good thermal stability and density. Furthermore, the MLCC prepared using the ceramic dielectric material has good mechanical strength, dielectric properties and reliability.
[0006] The inventive concept of the present invention is as follows: the ceramic dielectric material of the present invention comprises BaTiO3 and a eutectic; the elements in the eutectic comprise Bi, Li, B and Ba. The addition of Bi can form a low melting point eutectic Ba-Bi, which helps to reduce the sintering temperature and promote the wetting and rearrangement of grains; the addition of Li can further form Bi-Li and Ba-Bi-Li eutectics, further reducing the sintering temperature, and Li + The smaller radius can enter the BaTiO3 lattice and replace part of Ba 2+ or Ti 4+ ions, relieve lattice stress and reduce lattice distortion, promote material densification, and thus improve dielectric properties; the addition of B element can form eutectics of Ba-Bi-B, Bi-Li-B, and Ba-Bi-Li-B, further reduce the sintering temperature and fill the grain boundary pores, control the viscosity and fluidity of the liquid phase, prevent over-sintering or abnormal grain growth, pressurize to enhance contact between grains and promote uniform distribution of the liquid phase to avoid local accumulation and stagnant flow, and adjust the sintering behavior to ensure the density of the material. The present invention uses the combined action of BaTiO3 and eutectics to make the ceramic dielectric material have good thermal stability and density, and thus the prepared MLCC has good mechanical strength, dielectric properties and reliability.
[0007] Accordingly, a first aspect of the present invention provides a ceramic dielectric material.
[0008] Specifically, the ceramic dielectric material includes BaTiO3 and a eutectic; the elements in the eutectic include Ba, Bi, Li and B.
[0009] Preferably, the eutectic includes at least one of Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-B, Bi-Li-B, and Ba-Bi-Li-B eutectics.
[0010] Further preferably, the eutectic includes Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-B, Bi-Li-B and Ba-Bi-Li-B eutectic.
[0011] Preferably, the molar ratio of the BaTiO3 to the Bi element in the eutectic is (4.5-11):1; further preferably, the molar ratio of the BaTiO3 to the Bi element in the eutectic is (5-10):1.
[0012] Preferably, the molar ratio of the Bi element, the Li element and the B element is (3.5-5.5):(1.8-3.3):1; further preferably, the molar ratio of the Bi element, the Li element and the B element is (4-5):(2-3):1.
[0013] Specifically, taking the molar amount of the main component BaTiO3 as a comparison, if the amount of Bi element added is too large, too much liquid phase will be generated at the grain boundary of the main component, and the residual excess Bi will affect the formation of eutectic in the subsequent sintering process, and the degree of densification will decrease, affecting the reliability of the prepared MLCC, resulting in a decrease in breakdown strength and bending strength; if the amount of Bi element added is too small or no addition, no Bi-containing eutectic will be generated, which will cause the thermal stability and dielectric constant of MLCC to decrease; if the amount of Li or B added is too large (equivalent to too little Bi added), it will affect the sintering process temperature and the formation of the corresponding eutectic; if the amount of Li added is too small or no addition, the lattice distortion cannot be reduced, which will affect the density and dielectric properties; if the amount of B added is too small or no addition, the thermal stability, dielectric constant and reliability will be affected.
[0014] The second aspect of the present invention provides a method for preparing the ceramic dielectric material described in the first aspect of the present invention.
[0015] Specifically, the method for preparing the ceramic dielectric material comprises the following steps:
[0016] The ceramic dielectric material is obtained by mixing a Bi-containing compound, a B-containing compound, a Ba-containing compound, a Li-containing compound and BaTiO3, and sintering the mixture; and the Ba-containing compound does not include barium titanate.
[0017] Preferably, the method for preparing the ceramic dielectric material comprises the following steps:
[0018] (1) BaTiO3, a Bi-containing compound, and a Ba-containing hydrated compound are mixed and sintered for the first time to obtain a first powder;
[0019] (2) mixing the Li-containing compound and the first powder obtained in step (1), and performing a second sintering to obtain a second powder;
[0020] (3) Mixing the B-containing compound and the second powder obtained in step (2), and simultaneously pressurizing and sintering for a third time to obtain the ceramic dielectric material.
[0021] Preferably, in step (1), the Bi-containing compound includes at least one of Bi(OH)3, Bi2O3, BiCl3, and BiCl3·H2O.
[0022] Preferably, in step (1), the Ba-containing crystalline water compound includes H2BaO2·xH2O, and x is 1 or 8.
[0023] Specifically, the Ba-containing crystalline water compound includes at least one of Ba(OH)2·H2O and Ba(OH)2·8H2O.
[0024] Preferably, in step (2), the Li-containing compound includes at least one of Li2CO3, Li2O, LiCl·H2O, LiCl, LiOH, and LiOH·H2O.
[0025] Preferably, in step (3), the B-containing compound includes at least one of B2O3 and BCl3.
[0026] Preferably, the particle size ratio of the BaTiO3 to the Bi-containing compound is (1.5-5.5):1; further preferably, the particle size ratio of the BaTiO3 to the Bi-containing compound is (1.67-5):1.
[0027] Preferably, the particle size ratio of the Bi-containing compound to the Li-containing compound is (1.4-6.5):1; further preferably, the particle size ratio of the Bi-containing compound to the Li-containing compound is (1.5-6):1.
[0028] Preferably, the particle size ratio of the Li-containing compound to the B-containing compound is (1.8-8.5):1; further preferably, the particle size ratio of the Li-containing compound to the B-containing compound is (2-8):1.
[0029] Specifically, in the process of preparing the ceramic dielectric material of the present invention, the particle sizes of the Bi-containing compound, the Li-containing compound, and the B-containing compound decrease in sequence, which helps to achieve controllable regulation of the reaction rate and diffusion behavior during the sintering process. Bi with a larger particle size first forms a liquid phase, and the moderate Li then penetrates and interacts with Bi, while B with the smallest particle size is added in the final stage to ensure that all pores are filled, which helps to form a dense glass phase. The gradually decreasing particle size distribution ensures that each step of the chemical reaction and physical process can be fully carried out, and finally a highly densified sintered body is achieved.
[0030] Preferably, in step (1), the temperature of the first sintering is 200-400° C., and the holding time of the first sintering is 3-5 h.
[0031] Preferably, in step (2), the temperature of the second sintering is 400-600° C., and the holding time of the second sintering is 3-5 h.
[0032] Preferably, in step (3), the temperature of the third sintering is 600-800° C., the pressure of the third sintering is 200-500 MPa, and the holding time of the third sintering is 3-5 h.
[0033] Specifically, in the process of preparing ceramic dielectric materials, Ba-containing hydrated crystals are introduced under low temperature to form a liquid medium under high pressure, which promotes the rearrangement of material particles, dissolution-precipitation process and grain boundary migration. Compared with the traditional sintering temperature (above 900°C), it can achieve sintering at low temperature and obtain materials with good density. The specific mechanism is as follows: Ba-containing hydrated crystals have high solubility and provide sufficient Ba. 2+ and alkaline environment, dissolve some BaTiO3 precipitate particles in alkaline environment to form a saturated solution, sufficient Ba 2+ Make the barium source sufficient, Ba 2+ Diffusion will interact with TiO3 in solution 2- Combined, precipitated to form a new BaTiO3 phase, further recrystallized and deposited at the grain boundaries to fill the pores between the grain boundaries, promoting the growth and densification of the grains, and in an alkaline environment, it can simultaneously inhibit the formation of the secondary phase BaCO3, so as to better control the phase purity and stability of the recrystallization.
[0034] The Bi-containing compound is used as a low melting point sintering aid to form a low melting point eutectic Ba-Bi, which helps to reduce the sintering temperature and promote the wetting and rearrangement of the grains. The Li-containing compound is added to further form Bi-Li and Ba-Bi-Li eutectics, which further reduce the sintering temperature. + The radius is small, and it can enter the BaTiO3 lattice and replace part of Ba 2+ or Ti 4+ Ions, relieve lattice stress and reduce lattice distortion, promote material densification, and thus improve dielectric properties; compounds containing B are added to form eutectics of Ba-Bi-B, Bi-Li-B, and Ba-Bi-Li-B, further reducing the sintering temperature and filling the grain boundary pores, controlling the viscosity and fluidity of the liquid phase, preventing over-sintering or abnormal grain growth, pressurizing to enhance contact between grains and promote uniform distribution of the liquid phase, avoiding local accumulation and stagnant flow, and adjusting the sintering behavior to ensure the density of the material. The order of addition cannot be changed. Based on the order and composition of the formation of the eutectic, the eutectic is more likely to be enriched at the grain boundary after Bi is added, providing lubrication and preliminary densification basis for the entire sintering system components, facilitating the subsequent formation of eutectics in a gradually increasing temperature range after the addition of Li and B. After Li is added, it enters the lattice, relieves stress, adjusts the lattice structure, further densifies the material, and makes the sintering more uniform and controllable. Then B is added to form a glass phase, and the fluidity of the liquid phase is adjusted to make it distributed at the grain boundaries, ensuring that all pores are completely filled, thereby improving the uniformity of liquid phase distribution and material stability.
[0035] Preferably, the ratio of the heating rate of the first sintering, the heating rate of the second sintering and the heating rate of the third sintering is 1:(1-5):(2-7.5); further preferably, the ratio of the heating rate of the first sintering, the heating rate of the second sintering and the heating rate of the third sintering is 1:(2-5):(3-7.5).
[0036] Specifically, the heating rate of the first sintering is 2-5°C / min, the heating rate of the second sintering is 5-10°C / min, and the heating rate of the third sintering is 10-15°C / min.
[0037] Specifically, the heating rate during sintering can control the speed of grain growth, so that different types of eutectics can be generated in sequence within a specific sintering range, ensuring the density and thermal stability of the ceramic dielectric material. If the ratio range of the above heating rate is too large, it will cause the grains to grow too fast per unit time, and excessive growth or abnormal growth will form an uneven microstructure, affecting the density and thermal stability of the ceramic dielectric material. In addition, a too high heating rate is prone to phase change and the generation of secondary phases, such as BaCO3, which affects the purity of the ceramic dielectric material and further adversely affects the mechanical properties, dielectric properties and reliability of the MLCC. A heating rate with a ratio range that is too small will cause the eutectic to fail to completely form a liquid phase in sequence or within the specified sintering time, affecting the sintering process, and the pores cannot be completely filled, which is prone to uneven distribution of the added phase and poor sintering densification.
[0038] A third aspect of the present invention provides a multilayer ceramic capacitor.
[0039] Specifically, the multilayer ceramic capacitor includes the ceramic dielectric material described in the first aspect of the present invention.
[0040] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0041] (1) The ceramic dielectric material of the present invention includes BaTiO3 and a eutectic; the elements in the eutectic include Bi, Li, B and Ba. The addition of Bi, Li and B in the present invention can form eutectics of Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-B, Bi-Li-B and Ba-Bi-Li-B. Through the combined effect of BaTiO3 and the eutectic, the ceramic dielectric material of the present invention has good thermal stability and density, thereby making the prepared MLCC have good mechanical strength, dielectric properties and reliability.
[0042] (2) In the process of preparing the ceramic dielectric material of the present invention, a Bi-containing compound, a Li-containing compound, and a B-containing compound are added in sequence, and the order of addition cannot be changed. In addition, the particle sizes of the Bi-containing compound, the Li-containing compound, and the B-containing compound decrease in sequence, which helps to achieve controllable regulation of the reaction rate and diffusion behavior during the sintering process. The gradually decreasing particle size distribution ensures that each step of the chemical reaction and physical process can be fully carried out, and finally a ceramic dielectric material with good thermal stability and density is obtained.
[0043] (3) The present invention adopts a sequentially increasing heating rate during sintering. The heating rate can control the speed of grain growth, so that different types of eutectics can be generated sequentially within a specific sintering range, thereby ensuring the density and thermal stability of the ceramic dielectric material.
[0044] (4) In the process of preparing ceramic dielectric materials, Ba-containing hydrated crystals are introduced under low temperature to form a liquid medium under high pressure to promote the rearrangement of material particles, the dissolution-precipitation process and the grain boundary migration. Compared with the traditional sintering temperature (above 900°C), low temperature sintering can be achieved to obtain ceramic dielectric materials with good density. DETAILED DESCRIPTION
[0045] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0046] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0047] The types and amounts of the raw material components in Examples 1-15 and Comparative Examples 1-6 of the present invention are shown in Table 1.
[0048] The particle sizes of the raw material components in Examples 1-15 of the present invention and Comparative Examples 1-6 and the heating rates during the sintering process are shown in Table 2.
[0049] Table 1: Types and amounts (molar ratio) of various raw material components in Examples 1-15 and Comparative Examples 1-6 of the present invention
[0050]
[0051]
[0052] In Table 1, the molar ratio of Ti:Bi is the molar ratio of the Ti element content in BaTiO3 to the Bi element content in the Bi-containing compound, and Bi:Li:B is the molar ratio of the Bi element, Li element, and B element contents in the Bi-containing compound, the Li-containing compound, and the B-containing compound.
[0053] Table 2: Particle size of each raw material component and heating rate during sintering process in Examples 1-15 of the present invention and Comparative Examples 1-6
[0054]
[0055] In Table 2, X represents the particle size of BaTiO3 (μm), Y represents the particle size of the compound containing Bi (μm), Z represents the particle size of the compound containing Li (μm), E represents the particle size of the compound containing B (μm), and V1 represents the heating rate of the first sintering (℃·min -1 ), V2 represents the heating rate of the second sintering (℃·min -1 ), V3 represents the heating rate of the third sintering (℃·min -1 ).
[0056] Example 1
[0057] A method for preparing a ceramic dielectric material comprises the following steps:
[0058] (1) According to the molar ratio in Table 1, weigh barium titanate powder with a particle size of 0.08 μm and Bi(OH)3 with a particle size of 0.04 μm, add Ba(OH)2·8H2O (the molar ratio to the barium titanate powder is 0.05:1), mix well, and then perform the first sintering at a sintering temperature T1 of 300°C, a heating rate V1 of 2°C / min, and a holding time of 4 h to obtain a first powder for standby use;
[0059] (2) adding Li2CO3 with a particle size of 0.02 μm to the first powder obtained after the first sintering in step (1), mixing them evenly under ultrasonic vibration treatment, placing them under the condition of sintering temperature T2 of 500°C for a second sintering, heating rate V2 of 5°C / min, holding time of 4h, to obtain a second powder for standby use;
[0060] (3) Add B2O3 with a particle size of 0.01 μm to the second powder after the second sintering obtained in step (2), mix them evenly under ultrasonic vibration treatment, and place them at a sintering temperature T3 of 700°C and a constant pressure of 400 MPa for the third sintering. The heating rate V3 is 10°C / min and the insulation time is 4 hours to obtain a ceramic dielectric material.
[0061] Example 2
[0062] The only difference between Example 2 and Example 1 is that in Example 2, the molar ratio of Ti:Bi is 5, the compound containing Bi is Bi2O3, and the compound containing Li is Li2O, and the rest is the same as Example 1.
[0063] Example 3
[0064] The only difference between Example 3 and Example 1 is that in Example 3, the molar ratio of Ti:Bi is 10, the compound containing Bi is BiCl3, the compound containing Li is LiCl·H2O, and the compound containing B is BCl3, and the rest is the same as Example 1.
[0065] Example 4
[0066] The only difference between Example 4 and Example 1 is that in Example 4, the Bi-containing compound is BiCl3·H2O, the Li-containing compound is LiCl, the B-containing compound is BCl3, the molar ratio of Bi:Li:B is 4:2:1, and the rest is the same as Example 1.
[0067] Example 5
[0068] The only difference between Example 5 and Example 1 is that in Example 5, the Li-containing compound is LiOH, the molar ratio of Bi:Li:B is 4:3:1, and the rest is the same as Example 1.
[0069] Example 6
[0070] The only difference between Example 6 and Example 1 is that in Example 6, the compound containing Li is LiOH·H2O, the compound containing B is BCl3, the molar ratio of Bi:Li:B is 5:2:1, and the rest is the same as Example 1.
[0071] Example 7
[0072] The only difference between Example 7 and Example 1 is that in Example 7, the molar ratio of Bi:Li:B is 5:3:1, and the rest is the same as Example 1.
[0073] Example 8
[0074] The only difference between Example 8 and Example 1 is that in Example 8, the crystalline hydrate containing Ba is Ba(OH)2·H2O, and the rest is the same as Example 1.
[0075] Example 9
[0076] The only difference between Example 9 and Example 1 is that in Example 9, the particle size of X is 0.1 μm, X:Y is 1.67:1, and Y:Z is 1.5:1. The rest is the same as in Example 1.
[0077] Example 10
[0078] The only difference between Example 10 and Example 1 is that in Example 10, the particle size of X is 0.1 μm, X:Y is 1.67:1, Y:Z is 1.5:1, and Z:E is 8:1, and the rest is the same as in Example 1.
[0079] Embodiment 11
[0080] The only difference between Example 11 and Example 1 is that in Example 11, the particle size of X is 0.1 μm, X:Y is 1.67:1, and Y:Z is 6:1. The rest is the same as Example 1.
[0081] Example 12
[0082] The only difference between Example 12 and Example 1 is that in Example 12, the particle size of X is 0.1 μm, and the ratio of X:Y is 5:1. The rest is the same as in Example 1.
[0083] Embodiment 13
[0084] The only difference between Example 13 and Example 1 is that in Example 13, the particle size of X is 0.05 μm, and X:Y is 2.5:1. The rest is the same as in Example 1.
[0085] Embodiment 14
[0086] The only difference between Example 14 and Example 1 is that in Example 14, V1 is 5°C·min -1 , V1:V2:V3 is 1:2:3, and the rest is the same as in Example 1.
[0087] Embodiment 15
[0088] The only difference between Example 15 and Example 1 is that in Example 15, V1:V2:V3 is 1:5:7.5, and the rest is the same as Example 1.
[0089] Comparative Example 1
[0090] The only difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the molar ratio of Ti:Bi is 4, and the rest is the same as Example 1.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the molar ratio of Ti:Bi is 11, and the rest is the same as Example 1.
[0093] Comparative Example 3
[0094] The only difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the molar ratio of Bi:Li:B is 6:3:1, and the rest is the same as Example 1.
[0095] Comparative Example 4
[0096] The only difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, no Bi-containing compound is added, that is, the molar ratio of Bi:Li:B is 0:2.5:1, and the rest is the same as in Example 1.
[0097] Comparative Example 5
[0098] The only difference between Comparative Example 5 and Example 1 is that no Li-containing compound is added in Comparative Example 5, that is, the molar ratio of Bi:Li:B is 4.5:0:1, and the rest is the same as Example 1.
[0099] Comparative Example 6
[0100] The only difference between Comparative Example 6 and Example 1 is that no B-containing compound is added in Comparative Example 6, that is, the molar ratio of Bi:Li:B is 4.5:2.5:0, and the rest is the same as Example 1.
[0101] Performance Testing
[0102] The thermal stability and density tests were performed on the ceramic dielectric materials prepared in Examples 1-15 and Comparative Examples 1-6. In addition, the MLCCs prepared using the ceramic dielectric materials in Examples 1-15 and Comparative Examples 1-6 were tested for bending strength (mechanical strength), dielectric constant and breakdown strength (reliability).
[0103] The test methods and qualification standards for each test item are shown in Table 3.
[0104] Table 3: Test methods and qualification criteria for each test item
[0105]
[0106] The test results of thermal stability and density of the ceramic dielectric materials of Examples 1-15 and Comparative Examples 1-6, and flexural strength, dielectric constant and breakdown strength of MLCCs prepared from the ceramic dielectric materials of Examples 1-15 and Comparative Examples 1-6 are shown in Table 4.
[0107] Table 4: Thermal stability, density, flexural strength, dielectric constant and breakdown strength test results
[0108]
[0109]
[0110] It can be seen from Table 4 that the ceramic dielectric materials prepared in Examples 1-15 of the present invention have good thermal stability and density, and the MLCC prepared from the ceramic dielectric materials in Examples 1-15 of the present invention have good bending strength, dielectric properties, and breakdown strength, that is, the ceramic dielectric materials have strong thermal stability and good density, and the mechanical strength, dielectric properties and reliability of the prepared MLCC are better.
[0111] In Comparative Example 1, the molar ratio of Ti:Bi is 4. At this time, the relative content of Bi element is too high, so that the thermal stability and density of the ceramic dielectric material of Comparative Example 1 are worse than those of Example 1. The flexural strength and dielectric properties of the prepared MLCC are worse than those of the MLCC prepared in Example 1, especially the density and dielectric properties do not meet the qualified standards, and the material density and MLCC performance are unqualified.
[0112] In Comparative Example 2, the molar ratio of Ti:Bi is 11, and the relative content of the Bi element is too low, so that the thermal stability and density of the ceramic dielectric material of Comparative Example 2 are worse than those of Example 1, and the flexural strength and dielectric properties of the prepared MLCC are worse than those of the MLCC prepared in Example 1, and the thermal stability, density, flexural strength and dielectric properties do not meet the qualified standards, and the material stability and MLCC performance are unqualified.
[0113] Comparative Examples 1 and 2 show that the molar ratio of Ti:Bi must satisfy a certain proportional relationship. If the molar ratio is too large or too small, it will affect the stability and density performance of the ceramic dielectric material, and thus affect the performance of the MLCC.
[0114] In Comparative Example 3, the molar ratio of Bi:Li:B is 6:3:1, that is, the relative content of Bi is too large, so that the thermal stability and density of the ceramic dielectric material in Comparative Example 3 are worse than those in Example 1, and the bending strength, dielectric properties, and breakdown strength of the prepared MLCC are worse than those of the MLCC prepared in Example 1, and the density, bending strength, and breakdown strength do not meet the qualified standards, and the material density and MLCC performance are unqualified. This shows that the molar ratio of Bi:Li:B needs to meet a certain proportional relationship, and the stability and density of the prepared ceramic dielectric material are good, and the prepared MLCC has good performance.
[0115] No Bi-containing compound was added in Comparative Example 4, so that the thermal stability and density of the ceramic dielectric material of Comparative Example 4 were worse than those of Example 1, and the flexural strength and dielectric properties of the prepared MLCC were worse than those of the MLCC prepared in Example 1, and the thermal stability, density and dielectric properties did not meet the qualified standards and were unqualified.
[0116] In Comparative Example 5, no Li-containing compound is added, so that the thermal stability and density of the ceramic dielectric material of Comparative Example 5 are worse than those of Example 1. The bending strength and dielectric properties of the prepared MLCC are worse than those of the MLCC prepared in Example 1, and the density and dielectric properties do not meet the qualified standards and are unqualified.
[0117] No B-containing compound was added in Comparative Example 6, so that the thermal stability and density of the ceramic dielectric material of Comparative Example 6 were worse than those of Example 1, and the flexural strength, dielectric properties, and breakdown strength of the prepared MLCC were worse than those of the MLCC prepared in Example 1, and the thermal stability, density, dielectric properties, and breakdown strength did not meet the qualification standards and were unqualified.
[0118] Comparative Examples 4-6 show that Bi, Li and B must exist at the same time. The lack of any one of them will affect the thermal stability and density of the ceramic dielectric material, and thus affect the performance of MLCC.
[0119] In summary, the addition of Bi, Li and B elements in the present invention can form eutectics of Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-B, Bi-Li-B and Ba-Bi-Li-B. Through the combined action of BaTiO3 and the eutectic, the ceramic dielectric material has good thermal stability and density. In addition, by adding specific elements for sintering in different low temperature ranges and adopting a step-by-step controllable low temperature sintering technology, a thermally stable and highly densified barium titanate ceramic dielectric material can be obtained, thereby obtaining an MLCC with high mechanical strength, excellent dielectric properties and reliability.
[0120] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A ceramic dielectric material, characterized in that: Including BaTiO3 and eutectic; The elements in the eutectic include Ba element, Bi element, Li element and B element.
2. The ceramic dielectric material according to claim 1, characterized in that The eutectic includes at least one of Ba-Bi, Bi-Li, Ba-Bi-Li, Ba-Bi-B, Bi-Li-B, and Ba-Bi-Li-B eutectics.
3. The ceramic dielectric material according to claim 1, characterized in that The molar ratio of the BaTiO3 to the Bi element in the eutectic is (4.5-11):
1.
4. The ceramic dielectric material according to claim 1, characterized in that The molar ratio of the Bi element, the Li element and the B element is (3.5-5.5):(1.8-3.3):
1.
5. The method for preparing a ceramic dielectric material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The ceramic dielectric material is obtained by mixing a Bi-containing compound, a B-containing compound, a Ba-containing compound, a Li-containing compound and BaTiO3, and sintering the mixture; and the Ba-containing compound does not include BaTiO3.
6. The preparation method according to claim 5, characterized in that: The following steps are involved: (1) BaTiO3, a Bi-containing compound, and a Ba-containing hydrated compound are mixed and sintered for the first time to obtain a first powder; (2) mixing the Li-containing compound and the first powder obtained in step (1), and performing a second sintering to obtain a second powder; (3) Mixing the B-containing compound and the second powder obtained in step (2), and simultaneously pressurizing and sintering for a third time to obtain the ceramic dielectric material.
7. The preparation method according to claim 6, characterized in that: In step (1), the Bi-containing compound includes at least one of Bi(OH)3, Bi2O3, BiCl3, and BiCl3·H2O; and / or, the Ba-containing hydrate of crystallization compound includes H2BaO2·xH2O, and x is 1 or 8; And / or, in step (2), the Li-containing compound includes at least one of Li2CO3, Li2O, LiCl·H2O, LiCl, LiOH, and LiOH·H2O; And / or, in step (3), the B-containing compound includes at least one of B2O3 and BCl3.
8. The preparation method according to claim 6, characterized in that: The particle size ratio of the BaTiO3 to the Bi-containing compound is (1.5-5.5):1; and / or, the particle size ratio of the Bi-containing compound to the Li-containing compound is (1.4-6.5):1; And / or, the particle size ratio of the Li-containing compound to the B-containing compound is (1.8-8.5):
1.
9. The preparation method according to claim 6, characterized in that: In step (1), the temperature of the first sintering is 200-400° C., and the holding time of the first sintering is 3-5 hours; And / or, in step (2), the temperature of the second sintering is 400-600° C., and the holding time of the second sintering is 3-5 h; And / or, in step (3), the temperature of the third sintering is 600-800° C., the pressure of the third sintering is 200-500 MPa, and the holding time of the third sintering is 3-5 h; And / or, the ratio of the heating rate of the first sintering, the heating rate of the second sintering and the heating rate of the third sintering is 1:(1-5):(2-7.5).
10. A multilayer ceramic capacitor, characterized in that: The ceramic dielectric material comprises the ceramic dielectric material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ceramic dielectric material matched with nickel inner electrode and production method of capacitor produced by ceramic dielectric material
CN101786864A
High-dielectric-constant X8R type barium titanate-based dielectric material and preparation method thereof
CN113754427A
Tunable dielectric compositions including low loss glass
US20030073565A1
Low-temperature sintered barium titanate microwave dielectric ceramic material
US20060194691A1
Multilayer ceramic capacitor and method for producing multilayer ceramic capacitor
WO2021157151A1